Greš stavit? - predstavitev sinove raziskovalne naloge - Kuzman, Uroš (Obzornik za matematiko in fiziko, 2025)
The paper presents a primary school research project in mathematics, conducted by the author’s son under his supervision. The central focus of the project is sports betting, with the aim of developing a simple method for calculating betting odds for football matches in the English league. In addition to the project’s content, the article also discusses the pedagogical challenges faced by the author in mentoring a primary school student and his own child.
Keywords: football; igre na srečo; matematika; mathematics; nogomet; probability; sports betting; verjetnost